Palaeobiology of Hyaenodon exiguus (Hyaenodonta, Mammalia) based on morphometric analysis of the bony labyrinth. Issue 2 (25th September 2016) - Pfaff, Cathrin; Nagel, Doris; Gunnell, Gregg; Weber, Gerhard W.; Kriwet, Jürgen; Morlo, Michael; Bastl, Katharina
Abstract: Species of the extinct genus Hyaenodon were among the largest carnivorous mammals from the Late Eocene through Early Miocene in North America, Europe and Asia. The origin, phylogeny and palaeobiology of Hyaenodonta are still ambiguous. Most previous studies focused on teeth and dental function in these highly adapted species, which might be influenced by convergent morphologies. The anatomy of the bony labyrinth in vertebrates is generally quite conservative and, additionally, was used in functional–morphological studies. This study provides the first anatomical description of the bony labyrinth of the extinct European species Hyaenodon exiguus in comparison to selected extant carnivoran taxa discussed from a functional–morphological perspective. Hyaenodon exiguus may have occupied a hyaena‐like dietary niche with a semi‐arboreal lifestyle, based on the relative height, width and length of the semicircular canals of the inner ear. However, this contradicts previous functional–morphological studies focusing on the diameter of the canals, which presumably represent the signal of locomotion mode.